2014
DOI: 10.1128/iai.01546-13
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Protein G Is an Essential Virulence Factor of Leptospira interrogans

Abstract: e Leptospira interrogans is a global zoonotic pathogen and is the causative agent of leptospirosis, an endemic disease of humans and animals worldwide. There is limited understanding of leptospiral pathogenesis; therefore, further elucidation of the mechanisms involved would aid in vaccine development and the prevention of infection. HtpG (high-temperature protein G) is the bacterial homolog to the highly conserved molecular chaperone Hsp90 and is important in the stress responses of many bacteria. The specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 67 publications
(105 reference statements)
0
26
0
1
Order By: Relevance
“…Leptospira burdens in kidneys and liver were determined by qPCR, as previously described (35,44), with the following modifications. The Leptospira Manilae wild-type, lpxD1 mutant, and lpxD1 complemented mutant strains were injected intraperitoneally into groups of 4 gerbils (10 4 bacteria per animal).…”
Section: Figmentioning
confidence: 99%
“…Leptospira burdens in kidneys and liver were determined by qPCR, as previously described (35,44), with the following modifications. The Leptospira Manilae wild-type, lpxD1 mutant, and lpxD1 complemented mutant strains were injected intraperitoneally into groups of 4 gerbils (10 4 bacteria per animal).…”
Section: Figmentioning
confidence: 99%
“…Previous studies have identified a number of biological processes that appear to be required for leptospiral virulence. These include genes involved in motility (30,36), heme utilization (18), lipopolysaccharide biosynthesis (40), stress resistance (25,41,42), and the host-pathogen interaction (43) and genes that are involved in a manner that has not yet been determined (44,45). However, previous research has also negated the requirement of putative virulence factors LipL32 (46), LipL41 (47), and LigB (48) in the animal infection model.…”
Section: Fig 4 the Lb139mentioning
confidence: 94%
“…Binding of L. interrogans Mce was also observed with the human leukocyte cell receptors alphaLbeta2 [(CD11a/CD18)-LFA-1] and alphaMbeta2 [(CD11b/CD18)-Mac-1], suggesting the participation of these proteins in the induction of host immune response . These and other studies (Oliveira et al, 2010;Lehmann et al, 2013;King et al, 2014) suggest that virulence of pathogenic Leptospira is mediated by a combination of factors derived from both the pathogen and susceptible host.…”
Section: Virulence Factorsmentioning
confidence: 52%
“…Furthermore, a recent analysis of the binding receptors for LexA and transcript turnover following stress associated with genotypic toxicity in L. interrogans , suggest that potential shifts in gene expression occur following DNA damage, thereby downregulating genes involved in cell growth and virulence, but upregulating genes involved in generation of gene mutations and recombination . In addition, a previous study described the potential role of iron metabolism in Leptospira , and explained how the pathogen responds to oxidative stress (King et al, 2014). The results have collectively shown the potential of transcript analysis to determine the mechanisms utilized by Leptospira in causing disease.…”
Section: Advances On Transcriptomes Of Leptospiramentioning
confidence: 84%
See 1 more Smart Citation